2021
DOI: 10.1007/s00432-021-03562-1
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of prognostic factors in patients with nodular melanoma

Abstract: Purpose Nodular melanoma (NM) is associated with worse disease outcome when compared to superficial spreading melanoma (SSM). We aimed to perform a single-center analysis of prognostic factors in patients with NM and compare the data with SSM patients. Methods We studied 228 patients with NN and 396 patients with SSM. Patients with in situ melanomas or stage IV at diagnosis were not included in the study. Data were analyzed using the Mann–Whitney test, Chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…This, in fact, seems like a surprising finding, since the presence of DCD expression was also associated with a more favorable course of disease. As patients with NM and ALM subtypes often present with prognostically unfavorable tumors, one would have expected a different result (Susok and Gambichler 2021 ; Susok et al 2021 ). However, this finding could be partly explained by the proportion of patients with LMM having a relatively good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This, in fact, seems like a surprising finding, since the presence of DCD expression was also associated with a more favorable course of disease. As patients with NM and ALM subtypes often present with prognostically unfavorable tumors, one would have expected a different result (Susok and Gambichler 2021 ; Susok et al 2021 ). However, this finding could be partly explained by the proportion of patients with LMM having a relatively good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, a German single-center analysis observed that NM per se was not a significant independent predictor for disease recurrence or survival and was not associated with other unfavorable prognostic factors, including the absence of regression. 9 The epidemiological characteristics of ALMs are different from those of other types of cutaneous melanomas. ALM occurs more frequently in certain ethnic groups, such as blacks, Hispanics, and Asians, than in white-skinned persons (less than 5%).…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, a German single-center analysis observed that NM per se was not a significant independent predictor for disease recurrence or survival and was not associated with other unfavorable prognostic factors, including the absence of regression. 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In univariable analysis, nodular melanoma was found to have the lower OS. This is mainly due to its vertical growth pattern with a rapidly increasing Breslow depth [ 23 ]. Worst OS is confirmed for nodular melanoma also in multivariable analysis when adjusted to age and sex.…”
Section: Discussionmentioning
confidence: 99%